The Effect Of Compensation And Workload On Employee Loyalty At Bank Rakyat Indonesia Kaimana Unit - Musa Pakidi; Jacklyn Christy Patra Pakidi (Jurnal Indonesia Sosial Teknologi, 2023)
Compensation and workload are thought to influence employee loyalty. This research aims to determine the effect of compensation and workload on employee loyalty at Bank BRI Unit Kaimana. The data used in this research is quantitative data obtained through questionnaires for all 16 Bank BRI Unit Kaimana employees. Questionnaires were collected using Google Forms. Data were analysed using multiple linear regression with Excel. The results of this research are that compensation and workload have a significant effect on employee loyalty in different directions. Compensation positively affects employee loyalty, while workload hurts employee loyalty.